HMGB1 Mediates Autophagy Dysfunction via Perturbing Beclin1-Vps34 Complex in Dopaminergic Cell Model - Huang, Jinsha; Yang, Jiaolong; Shen, Yan; Jiang, Haiyang; Han, Chao; Zhang, Guoxin; Liu, Ling; Xu, Xiaoyun; Li, Jie; Lin, Zhicheng; Xiong, Nian; Zhang, Zhentao; et al. (Frontiers in Molecular Neuroscience, 2017)
Parkinson’s disease (PD), a progressive neurodegenerative disorder, is characterized by irreversible dopaminergic neuron loss and intra-neuronal α-synuclein aggregation. High mobility group box 1 (HMGB1) has been proven to be involved in autophagy dysfunction induced by α-synuclein accumulation, and the Beclin1-Vps34 complex is of great mportance to the initiation of autophagy. Nevertheless, the concrete interaction mechanism between HMGB1, α-synuclein and autophagy remains elusive, especially in the context of PD. Here in this study, we investigated the interaction between HMGB1 and α-synuclein in rotenone-induced PD cell models and their roles in autophagy flux. Results revealed elevated expression and cytosolic translocation of endogenous HMGB1 upon rotenone exposure. Besides, HMGB1 was found to be able to co-localize and interact with α-synuclein. Moreover, it had also been proven that HMGB1 could aggravate α-synuclein aggregation induced autophagy dysfunction via perturbing Beclin1-Vps34 complex formation. Based on these findings, we propose that HMGB1 is involved in rotenone-induced dopaminergic cell death via interacting with α-synuclein, perturbing the autophagy process, aggravating protein aggregation and finally propelling dopaminergic neurons to move from morbidity to mortality.